Chronic intermittent ethanol exposure in mice leads to an up-regulation of CRH/CRHR1 signaling - Eisenhardt, Manuela; Spanagel, Rainer (Alcoholism, 2015)
Background: One of the most commonly used approaches to induce ethanol (EtOH) dependence in rodents is EtOH vapor inhalation. This procedure requires the co-administration of pyrazole—an inhibitor of the alcohol dehydrogenase—to obtain stable blood EtOH concentrations (BECs) during the entire induction course. However, pyrazole can produce unwanted side effects. Our goal was to obtain EtOH-dependent mice without pyrazole and to study their behavioral and molecular postdependent phenotype. In particular, we were interested in alterations in the corticotrophin-releasing hormone (CRH) and receptor (CRHR1 and CRHR2) system as a prominent role of CRH in driving the postdependent state via actions in the central extended amygdala (CeA) has been demonstrated in rats but not in postdependent mice. Methods: We established an alternative model of chronic intermittent EtOH (CIE) inhalation without the use of pyrazole in C57BL/6N mice. Our CIE exposure protocol involved 8 cycles. One cycle consisted of 8 hours with EtOH inhalation and 8 hours without EtOH. We then examined withdrawal symptoms. After 2 weeks of abstinence, we studied relapse, reinstatement of EtOH-seeking, and stress-induced EtOH self-administration. We also did transcriptional analysis of components of the CRH system during CIE, protracted abstinence, and after stress-induced EtOH self-administration. Results: CIE exposure without pyrazole resulted in reproducible BECs during the induction procedure. Mice showed strong withdrawal scores during 4 to 12 hours after the last CIE cycle and enhanced stress-induced EtOH self-administration. This postdependent phenotype during abstinence was accompanied by enhanced Crh and Crhr1 transcripts but no change in Crhr2 transcripts in the CeA. Cue-induced EtOH-seeking behavior and relapse (alcohol deprivation effect) were not affected by the inhalation procedure. Conclusions: We have established a CIE inhalation protocol without pyrazole in mice and showed excessive EtOH self-administration under mild stress and enhanced CRH/CRHR1 signaling in the CeA.
Gesehen am 03.11.2017